Numerical Modeling the Rock Mass Stress-Strain State Near Vertical Excavations in Combined Mining - Zeitinova, Sh.; Imashev, A.; Bakhtybayev, N.; Matayev, A.; Mussin, A.; Yeskenova, G. (Salehan Institute of Higher Education, 2024)
In recent years, the development of the mining industry in the Republic of Kazakhstan has been accompanied by the commissioning of new underground levels for many existing mineral deposits, which were initially developed through open-pit mining. As the depth of open-pit mining increases, the volume of overburden rises sharply, making open-pit mining unprofitable due to the significant amount of additional mining work required. For this reason, most open-pit mines in Kazakhstan are transitioning to underground mining, or combined mining. Many researchers have examined the timing of this transition and have worked on optimizing it to determine the best economic efficiency and manage risks. However, there is limited information available on how to determine the optimal location for a vertical mine shaft when transitioning from open-pit to underground mining. The purpose of this study is to identify a safe location for a vertical shaft in combined mining operations. Specifically, the study assesses the impact of the open-pit mine on the selection of the mine shaft’s location, considering the stress-strain state of the rock mass during combined mining methods. To address these objectives, numerical modeling of the stress-strain state around vertical excavations during combined mining was performed. The results provide a solution to the critical issue of determining the location of the mine shaft in combined geotechnology and lay the groundwork for further research on shaft placement in Kazakhstan. The novelty of this study lies in identifying the shaft location by considering the geometric shape of the open-pit mine and the depth of development. Doi: 10.28991/CEJ-2024-010-09-010 Full Text: PDF